Pengaruh Brand Image terhadap minat nasabah dengan Korean Wave sebagai variable intervening (Case Studi Bank Kb Bukopin) - Vajri Rahman, Ahmad (Riset Sinergi Indonesia, 2022)
Brand image means things that can be seen or assessed even before consumers or people use a product or service, including how the brand can meet the social and psychological needs of consumers. Since being acquired by Kokmin Bank, Bank Kb Bukopin has issued a new slogan